Strategic Hedging and Middle Power Foreign Policy: The Case of Thailand as Viewed Through Neoclassical Realism - Mendiolaza, Gustavo Alejandro (Curtin University, 2023)
The Sino-American competition poses a challenge for all states, including Thailand. As a Southeast Asian middle power, Thailand must balance long-term security and short-term economic interests. Strategic hedging, deeply rooted in Thai history, involves engaging with competing great powers. This thesis explores Bangkok's foreign policy by examining its past, using neoclassical realist theory to analyze policy development and external factors. By studying centuries of strategy, this thesis fills a gap in literature on hedging and offers insights into Thailand's approach to the superpower rivalry.